Values Content in television advertisements directed at children / analytical study - Shaban, Afnan Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
The research deals with the analysis of the valuable content in television advertisements directed at children and aims to achieve several goals, including determining the type of advertisement used, the topics that are included in TV ads, the nature of the values in the advertisement and the grooming used in the advertisement and the methods used in advertisements directed at children, and a content analysis form was prepared that includes major and sub categories The research sample, which included the selection of a sample of TV ads targeted to children from the research community, analyzes the mbc1 channel and the mbc3 channel. The random sample consisted of (28) ads whose content was analyzed using The method of repetitions andpercentages, and reached several results, the most important of which is the diversity of topics that television advertisements provide for products related to children, which are his basic needs and his need to feel pleasure through games and other shows. The ads provide valuable values including assistance, love of goodness and aesthetic values, and the ads use logical and emotional conviction methods, Likewise, simulation, acting and singing techniques are used, and advertisements are concerned with attractions in presenting their promotional contents.